2018
DOI: 10.2460/ajvr.79.11.1166
|View full text |Cite
|
Sign up to set email alerts
|

Cell-mediated and humoral immune responses to bovine herpesvirus type 1 and bovine viral diarrhea virus in calves following administration of a killed-virus vaccine and bovine herpesvirus type 1 challenge

Abstract: OBJECTIVE To evaluate cell-mediated and humoral immune responses of calves receiving 2 doses of a dual-adjuvanted vaccine containing inactivated bovine herpesvirus type 1 (BHV1) and bovine viral diarrhea virus types 1 (BVDV1) and 2 (BVDV2) before and after exposure to BHV1. ANIMALS 24 Holstein steers negative for anti-BHV1 antibodies and proliferative cell-mediated immune responses against BHV1 and BVDV. PROCEDURES Calves were randomly assigned to 3 groups. The vaccinated group (n = 10) received 2 doses of vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…As previously discussed, antigenic similarity is typically determined using serological assays such as VNT, whereas CMI is generally determined by the induction of IL-2, IFN-γ, and CD25 labeling ( 25 27 , 29 , 30 ). To date, no studies have measured differences in CMI responses against multiple BVDV strains to better understand if there is a strain specific component to CMI or if it is a generalized cellular response to BVDV antigens and contributes to a more broadly protective response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously discussed, antigenic similarity is typically determined using serological assays such as VNT, whereas CMI is generally determined by the induction of IL-2, IFN-γ, and CD25 labeling ( 25 27 , 29 , 30 ). To date, no studies have measured differences in CMI responses against multiple BVDV strains to better understand if there is a strain specific component to CMI or if it is a generalized cellular response to BVDV antigens and contributes to a more broadly protective response.…”
Section: Discussionmentioning
confidence: 99%
“…Since the current assay evaluated mRNA expression and not protein accumulation, the timing post stimulation is targeted at IFN-γ which is typically involved in CMI responses and has previously been optimized for the current assay ( 27 ). Although, this is a limiting factor of the current assay as multiple cytokines cannot be measured, but in general, IFN-γ is a characteristic cytokine produced by memory T cells during an antigen recall response ( 25 27 , 29 , 30 , 39 , 40 ). To this end, IFN-γ mRNA expression may vary in the different PBMCs evaluated in the current study, the timing may also vary in each respective PBMC population, and each BVDV strain may vary in timing of induction of IFN-γ mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased protection provided by BVDV MLV vaccines is thought to be associated with a more robust CMI response as determined by cell-mediated recall responses measured by the production of IFN-γ and expression of CD25+ as markers for activated T-lymphocytes. Previous literature has suggested that both MLV and KV containing BVDV exhibit a recall memory response as observed by inducing increased expression of IFN-γ in T-cell subsets after re-stimulation with BVDV in vitro [ 25 , 26 , 27 ]. It should be noted that while it has been suggested that inactivated BVDV vaccines induce a CMI response, these results are discordant with the in vivo data that support that MLV vaccines induce a more effective response.…”
Section: Discussionmentioning
confidence: 99%